EDUKASI PIROLISIS SEBAGAI TEKNIK PENGOLAHAN SAMPAH PLASTIK BAGI SISWA SMA KANISIUS JAKARTA - Jaya, Arie Sukma; Mitan, Nona Merry Merpati; Nugroho, Agung; Hehamahwa, Arbhy Bramantya; Rizqita, Indy Inasa; Simanullang, Evelin Grace Elisabet; Maharana, Lintang Saksi; Harfilani, Rialfi Putri Nur; Nuraini, Nuraini (Jurnal Abdimas Musi Charitas, 2024)
Plastic waste can cause severe problems for the environment and humans. This is because plastic is rugged and degrades naturally. Inadequate plastic waste management in the community around SMA Kanisius is a challenge in overcoming plastic waste. This activity aims to increase student's awareness and knowledge of the importance of plastic waste processing through pyrolysis in overcoming the problem of plastic waste. SMA Kanisius can be a model school for plastic waste processing, from sorting plastic waste to processing plastic waste into liquid fractions through pyrolysis. The output of this activity is an increase in knowledge of students regarding the basic concept of pyrolysis technology as an alternative method of processing plastic waste. This community service activity shows the implementation of scientific and engineering knowledge in plastic waste processing in pyrolysis technology. This community service activity is expected to help open students' insights into plastic waste recycling so that awareness of processing plastic waste can be started in schools. Indirectly, this activity can have an impact on environmental maintenance.